SASTRA AL-QURâ€™AN DI TENGAH ALIRAN SASTRA INDONESIA - Syaifuddin, Helmi (Laboratorium Informasi & Publikasi Fakultas Humaniora UIN Maulana Malik Ibrahim Malang, 2006)
Throughout Indonesiaâ€™sÂ long history, the meaning of Indonesian art has been the subject of debate. Is just â€œart for arts sakeâ€, or is there a more obscure socio-political message behind the more obvious depictions. In socio-political context it would seem that Indonesian art expresses socio-political themes, but in examples depicting surrealism, absurdity, existentialsm, prophetic art and post-modernist etc. Indonesiaâ€™s art is nor a modern phenomenon. Indonesiaâ€™s art seems to continually focus on the more superficial; ideas without attempting to make even minor changes to past cultural influence. In this context therefore the emergence of a new paradigm is not surprising, and the emergence of a Koranic influence in Indonesian art is becoming the latest paradigm in interpreting the reality and meaning of contemporary indonesian art.